2015
DOI: 10.12688/f1000research.7111.1
|View full text |Cite
|
Sign up to set email alerts
|

ve-SEQ: Robust, unbiased enrichment for streamlined detection and whole-genome sequencing of HCV and other highly diverse pathogens

Abstract: The routine availability of high-depth virus sequence data would allow the sensitive detection of resistance-associated variants that can jeopardize HIV or hepatitis C virus (HCV) treatment. We introduce ve-SEQ, a high-throughput method for sequence-specific enrichment and characterization of whole-virus genomes at up to 20% divergence from a reference sequence and 1,000-fold greater sensitivity than direct sequencing. The extreme genetic diversity of HCV led us to implement an algorithm for the efficient desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 34 publications
4
86
0
Order By: Relevance
“…For the samples from volunteers with a history of acute HEV infection, HEV genotyping was performed at Public Health England Reference Laboratories or performed in‐house by nested reverse‐transcriptase PCR (RT‐PCR) on 10 μL of purified RNA using the Access kit (Promega, Southampton, UK) with primers as described . In 1 patient, HEV viremia was detected by RNA sequencing analysis as described . For the samples from chronically infected patients, HEV RNA was detected by a nested RT‐PCR as described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the samples from volunteers with a history of acute HEV infection, HEV genotyping was performed at Public Health England Reference Laboratories or performed in‐house by nested reverse‐transcriptase PCR (RT‐PCR) on 10 μL of purified RNA using the Access kit (Promega, Southampton, UK) with primers as described . In 1 patient, HEV viremia was detected by RNA sequencing analysis as described . For the samples from chronically infected patients, HEV RNA was detected by a nested RT‐PCR as described .…”
Section: Methodsmentioning
confidence: 99%
“…(43) In 1 patient, HEV viremia was detected by RNA sequencing analysis as described. (44) For the samples from chronically infected patients, HEV RNA was detected by a nested RT-PCR as described. (45) Nucleotide sequences were deduced from bulk PCR products and genotyped by comparison with HEV genotype 3 subtype reference sequences.…”
Section: Hev Viremia and Genotypingmentioning
confidence: 99%
“…Highly variable pathogens, particularly those that have widely divergent genetic lineages or genotypes, such as HCV 97 and norovirus, cause problems for PCR amplification, such as primer amplification 27,92 and primer mismatches 86 . Careful primer design may help to mitigate these problems, but novel variants remain problematic.…”
Section: Box 2 | Whole-genome Sequencing Of Zika Virusmentioning
confidence: 99%
“…This may originate through variability in the degree of match between probe or primer sets to the target viral sequence and therefore differences in the efficiency of target capture or amplification. We have recently shown that introducing probes to better represent known sequence variation can reduce bias in coverage due to probe-target divergence to zero (10). However, incomplete coverage was not a consistent problem for any of the capture methods, which in fact provided substantially greater depth of HCV coverage than metagenomic methods that were probe independent.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Oxford. As described previously (10,12), low-quality bases were trimmed from demultiplexed sequences using QUASR v7.01 (www.bioconductor.org/packages/release/bioc/html /QuasR.html), and adapter sequences were removed using CutAdapt v1.7.1 (http://cutadapt.readthedocs.io/en/stable/index.html). Human sequences were excluded by mapping to the HG19 human reference genomes with Bowtie v2.2.4 (http://bowtie-bio.sourceforge.net/index.shtml), and HCV-derived reads were aligned to a local BLAST database of 165 HCV genomes collated by the ICTV (International Committee on the Taxonomy of Viruses).…”
Section: Samplesmentioning
confidence: 99%